Probation Centers as Spaces of Implementing Children's Rights. A Polish Case Study - Anna Babicka-Wirkus (Vasyl Stefanyk Precarpathian National University, 2023)
A probation center is one of the educational measures provided in Polish law for socially maladjusted youth. It is a non-isolation form of social rehabilitation and preventive action, which enables young people who are at risk of demoralization to remain in the family and school environment. The current article concerns the potential that Polish probation centers have for realizing the idea of children's rights. It puts forward the following thesis: Probation centers are spaces for exercising children's rights as well as Janusz Korczak's pedagogy. Such centers follow the 3P principle (provision - protection - participation), which is included in the Convention on the Rights of the Child. Implementing this principle in probation centers makes it possible to establish a relationship between the probation officer/educator and the child/adolescent that is based on respect, openness, understanding, acknowledgment, ignorance, and love. These attitudes fit into Janusz Korczak's pedagogy, which is founded on the assumption that children have their rights as human beings and that adults are obligated to respect and protect these rights as well as to allow children to exercise them in everyday activities. As a non-isolating form of social rehabilitation interactions, the probation center does not contribute to the stigmatization of the child, but can be a safe place to practice the rights of the child and citizen.